Índice de prenhez com sêmen congelado de garanhões crioulos usando glicerol ou dimetilformamida como crioprotetores - Oliveira, Rodrigo Arruda de (2007)
During the 2005 and 2006 southern hemisphere natural breeding season, 104 Criollo mares were used to evaluate deep frozen semen fertility from 5 Criollo stallions. FR4 was used as extender (Nutricell, Brazil) with 5% glycerol (GLY) or 5% dimethylformamid (DMF) as cryoprotectants. Semen was loaded in 0.5mL straws (100x106 spermatozoa/straw). Mares were examined every other day by ultrasonography until detection of ≥30mm diameter follicles, when hCG was injected (2500UI i.v.). After 24 hours, mares were examined daily in Experiment I, and every 6 hours, in experiment II. Insemination with frozen semen was performed deep in the uterine horn ipsilateralis to the dominant follicle. Controls were inseminated with fresh semen in the body of the uterus. Only one estrus period per mare was used. Pregnancy diagnosis through ultrasonography was performed on the 15th day postovulation. In experiment I, pregnancy rates were 11.9% (5/42) and 62.5% (20/32), respectively for DMF and fresh semen (P<0.0001). In experiment II, pregnancy rates were 40% (4/10), 10% (1/10) and 70% (7/10), respectively for DMF, GLY (P>0.05) and fresh semen (P<0.0001). It was showed that GLY and DMF can be used for frozen of Criollo Stallion s semen. In this context DMF brought better results.